Las Enfermedades Reumáticas como Factor de Riesgo en el Desarrollo de la Leucoencefalopatía Multifocal Progresiva - Calderón Valverde, Gabriel (2020)
Multifocal progressive leukoencephalopathy, caused by reactivation of a latent JC-virus infection, has been classically correlated with certain conditions such as HIV infection, hematological malignancies and profound immunosuppression. Nevertheless, more recently, rheumatic autoimmune diseases have been identified as a risk factor for the development of this condition. Amongst these diseases, Systemic Erythematous Lupus stands out as the disease with greater incidence for PM; a remarkable superior prevalence which doesn’t seem to be related with pharmacological immunosuppression, but with inherent characteristics of the disease